Inhibition of HIV-1 infection with curcumin conjugated PEG-citrate dendrimer; a new nano formulation - Saeideh Ebrahimi; Majid Sadeghizadeh; Mohammad Reza Aghasadeghi; Mehdi Shafiee Ardestani; Shaghayegh Adib Amini; Roohollah Vahabpour (BMC, 2024)
Abstract Background Nano-drug delivery systems have become a promising approach to overcoming problems such as low solubility and cellular uptake of drugs. Along with various delivery devices, dendrimers are widely used through their unique features. PEG-citrate dendrimers are biocompatible and nontoxic, with the ability to improve drug solubility. Curcumin, a naturally occurring polyphenol, has multiple beneficial properties, such as antiviral activities. However, its optimum potential has been significantly hampered due to its poor water solubility, which leads to reduced bioavailability. So, the present study attempted to address this issue and investigate its antiviral effects against HIV-1. Method The G2 PEG-citrate dendrimer was synthesized. Then, curcumin was conjugated to it directly. FTIR, HNMR, DLS, and LCMS characterized the structure of products. The conjugate displayed an intense yellow color. In addition, increased aqueous solubility and cell permeability of curcumin were achieved based on flow cytometry results. So, it could be a suitable vehicle for improving the therapeutic applications of curcumin. Moreover, cell toxicity was assessed using XTT method. Ultimately, the SCR HIV system provided an opportunity to evaluate the level of HIV-1 inhibition by the curcumin-dendrimer conjugate using a p24 HIV ELISA kit. Results The results demonstrated a 50% up to 90% inhibition of HIV proliferation at 12 μm and 60 μm, respectively. Inhibition of HIV-1 at concentrations much lower than CC50 (300 µM) indicates a high potential of curcumin-dendrimer conjugate against this virus. Conclusion Thereby, curcumin-dendrimer conjugate proves to be a promising tool to use in HIV-1 therapy.